Online teaching practices and the effectiveness of the educational process in the wake of the COVID-19 pandemic - Cristina Venera Tartavulea; Catalin Nicolae Albu; Nadia Albu; Ramona Iulia Ţarţavulea; Silvia Petre (Amfiteatru Economic Journal, 2020)
In this paper, we investigate the impact of the abrupt switch to online teaching which occurred in 2020 due to the COVID-19 pandemic. By using responses from 362 professors and students from 13 European countries, we find that universities and students were very quick to adapt to the new changes and that a mix of synchronous and asynchronous interaction and assessment methods are currently employed. However, this mix is quite limited relative to what is usually subsumed into online learning tools, and is indicative of passive delivery and reduced interaction. Our respondents estimate that most online interaction and assessment methods will continue to be used after the return to face-to-face education. Our respondents also view the switch to online teaching to have an overall moderate positive impact on the educational process, albeit the overall effectiveness of the online educational experience is perceived to be lower than in the case of face-to-face teaching. Moreover, we find that the institutional support, the trust in the online system and the perceived effectiveness of formative assessment are factors that are positively associated with the impact and effectiveness of online education.
Keywords: A23; I23; 330; online teaching; quality of online education; effective online education; online instructional methods; online assessment methods